2010
DOI: 10.1007/s10753-010-9184-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intrapulmonary Expression of Inducible Nitric Oxide Synthase Gene and Nuclear Factor κB Activation in Severe Pancreatitis-associated Lung Injury

Abstract: The aim of this study is to explore the relationship of intrapulmonary activation of nuclear factor-kappaB (NF-kappaB) and the expression of inducible nitric oxide synthase (iNOS) mRNA with pulmonary injury in rats with severe acute pancreatitis (SAP). Fifty-four Sprague Dawley rats were randomly divided into three groups: sham operation (control) group (n = 18), SAP group (n = 18), and pyrrolindine dithiocarbamate (PDTC) pretreated group (n = 18). A SAP model was induced by retrograde injected 5% sodium tauro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…The reason why our data did not show the fully inhibitory effects of PDTC on ALI as others found [19,20] may be due to that PDTC was administered after LPS challenge as the therapeutic process to mimic the situation in clinic. It is also possible that PDTC has different effects between small and large animals, or that the severity of ALI in our model was more serious.…”
Section: Discussioncontrasting
confidence: 52%
“…The reason why our data did not show the fully inhibitory effects of PDTC on ALI as others found [19,20] may be due to that PDTC was administered after LPS challenge as the therapeutic process to mimic the situation in clinic. It is also possible that PDTC has different effects between small and large animals, or that the severity of ALI in our model was more serious.…”
Section: Discussioncontrasting
confidence: 52%
“…PDTC treatment further reduced the expression of iNOS mRNA and effectively improved the severity of lung injury. 122,123 Sphingosine-1-phosphate (S1P), a biological active lipid, reduces the NF-kB activation of alveolar macrophages, which leads to prevention of pancreatitis-associated lung injury. 124…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…PARP was involved in nuclear factor (NF)-κB expression and thereby activated NOS. ADP ribosylaion is required to activate NF-κB-mediated iNOS gene transcription [48,49]. Remick et al [50] also suggested that ADP ribosylation was crucial in the signaling pathway which leads to NOS mRNA expression.…”
Section: Discussionmentioning
confidence: 99%